Pendidikan Kesehatan Berbasis Media Terhadap Pengetahuan Ibu Hamil Tentang Tanda Bahaya Kehamilan Di Puskesmas Binanga Mamuju - Thalib, Kiki Uniatri; Rabuana, Susi; Darmansyah, Safriadi; D, Yuliana; Sallo, Andi Kamal M.; Parwati, Dewi; Susanti, Susanti (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Pregnant women who experience dangerous signs of pregnancy should immediately see the nearest health worker. If the health worker you meet is a midwife, the pregnant woman will receive emergency treatment and be immediately referred to the hospital for further treatment. Early detection of pregnancy complications can be used as an effort to prevent complications in pregnancy. The main problem at the Binanga Mamuju Community Health Center is that there are still many pregnant women who do not know the danger signs of pregnancy that they need to be aware of. Delay in detecting complications will be dangerous for the mother and fetus. The aim of this service is to increase pregnant women's knowledge about the danger signs of pregnancy. Method This activity was carried out using the counseling method, providing leaflets and discussions. Participants in this activity were 22 pregnant women at the Binanga Mamuju Community Health Center. To determine the effectiveness of this activity, participants were given a pretest and posttest to measure increased knowledge of the dangers of pregnancy. Evaluation Results The results obtained in this activity were that participants were very enthusiastic about following the counseling given and discussing so that there was an increase in knowledge as seen from the pre-test results from 7 (31.8) with good knowledge to 19 (86.4) with good knowledge about the danger signs of pregnancy. The success of this outreach was also due to the provision of attractively presented leaflets that used pictures and sentences that were easy for participants to understand. The results of this PKM assessment can be used as a benchmark for midwives that providing education in pregnancy about the danger signs of pregnancy is very important for the continuity of the mother's pregnancy.